Cognitive Load and AI-Assisted Learning in Thai Higher Education: A Structural Model Approach - Rungchatchadaporn Vehachart; Ratna Yunita Setiyani Subardjo (Advances in Psychological Sciences and Applications, 2026)
The integration of artificial intelligence (AI) in higher education has significantly transformed teaching and learning processes. While AI-assisted learning tools offer personalized feedback and adaptive learning environments, their cognitive implications remain underexplored, particularly in non-Western contexts. This study investigates the impact of AI-assisted learning on cognitive load and learning outcomes in Thai higher education. Using Cognitive Load Theory (CLT) as a framework, a quantitative approach with PLS-SEM was applied to data from 312 students. The findings indicate that AI-assisted learning reduces extraneous cognitive load while enhancing germane cognitive load. Student engagement mediates the relationship between cognitive load and learning outcomes, while cultural factors moderate AI usage effects.